Constructing Christian identity in 'Luke-Acts': the purpose of Pharisees in Lukan theology - Selvatici, Monica (Romanitas - Revista de Estudos Grecolatinos, 2017)
The purpose of this article is to analyze the references made by the author of the third gospel and the book of Acts (so-called Luke) to members of the Christian communities in the 1st century CE who defended that Christians had to fully observe Torah laws and who especially defended circumcision for Gentile Christians. Luke refers to them as ‘Pharisees’ in Acts 15, 5. Indirect allusions to these Christian Pharisees are ubiquitous in Luke’s work, showing that this issue was very important within his theology. When writing Luke-Acts, Luke was confronted with the sense of orphanhood of the Gentile Christian movement after the Apostle Paul’s death. Careful analysis of his books reveals more clearly the evangelist’s intent to convince his readers that the Gentile Christian movement is heir of the eschatological blessings promised to Judaism.
Keywords: Identidade cristã; Literatura cristã; Evangelho de Lucas; Atos dos Apóstolos; Fariseus